Intraoperative Spinal Angiography during Microsurgical Occlusion of Spinal Dural Arteriovenous Fistula within the Hybrid Operation Room - Kienzler, Jenny Christine; Schoepf, Salome; Marbacher, Serge; Diepers, Michael; Remonda, Luca; Fandino, Javier (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Spinal dural arteriovenous fistula (SDAVF) is a rare cause of progressive myelopathy in predominantly middle-aged men. Treatment modalities include surgical obliteration and endovascular embolization. In surgically treated cases, failure of obliteration is reported in up to 5%. The aim of this technical note is to present a safe procedure with complete SDAVF occlusion, verified by intraoperative digital subtraction angiography (DSA).Methods We describe four patients with progressive leg weakness who underwent surgical obliteration of SDAVF with spinal intraoperative DSA in the prone position after cannulation of the popliteal artery. All surgeries took place in our hybrid operating room (OR) and were accompanied by electrophysiologic monitoring. Surgeries and cannulation of the popliteal artery were performed in the prone position. Ultrasound was used to guide the popliteal artery puncture. A 5-Fr sheath was inserted and the fistula was displayed using a 5-Fr spinal catheter. Spinal intraoperative DSA was performed prior to and after temporary clipping of the fistula point as well after the final SDAVF occlusion.Results The main feeder of the SDAVF fistula in the first patient arose from the right T11 segmental artery, which also supplied the artery of Adamkiewicz. The second patient initially underwent endovascular treatment and deteriorated 5 months later due to recanalization of the SDAVF via a small branch of the T12 segmental artery. The third and fourth cases were primarily scheduled for surgical occlusion. Access through the popliteal artery for spinal intraoperative DSA proved to be beneficial and safe in the hybrid OR setting, allowing the sheath to be left in place during the procedure. During exposure and after temporary and permanent occlusion of the fistulous point, intraoperative indocyanine green (ICG) video angiography was also performed. In one case, the addition of intraoperative DSA showed failure of fistula occlusion, which was not visible with ICG angiography, leading to repositioning of the clip. Complete fistula occlusion was documented in all cases.Conclusion Spinal intraoperative DSA in the prone position is a feasible and safe intervention for rapid localization and confirmation of surgical SDAVF occlusion.
Keywords: spinal dural arteriovenous fistula; intraoperative DSA; hybrid operation room